A case of two foci of primary melanoma with metastasis to the skin in giant congenital melanocytic nevi - Fijałkowska, Marta; Nejc, Dariusz; Antoszewski, Bogusław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Congenital melanocytic nevi are moles that are present at birth or arise within the first weeks of life [1]. They vary in size, from small, medium to very large or giant ones (more than 20 cm in diameter) [1, 2]. Giant congenital melanocytic nevi occur in approximately 1 in 20 000–50 000 newborns [3]. It is established in the literature that patients with giant melanocytic nevus have an elevated risk of developing melanoma, which ranges from 2% to 42% in the literature [1–3]. To date, no universal guidelines to treat giant melanocytic nevi have been given [3].